Жупановское землетрясение 30.01.2016 г. c Ks = 15.7, Mw = 7.2, I= 6 (Камчатка) - Чебров В.Н.; Кугаенко Ю.А.; Абубакиров И.Р.; Дрознина С.Я.; Иванова Е.И.; Матвеенко Е.А.; Митюшкина С.В.; Ототюк Д.А.; Павлов В.М.; Раевская А.А.; Салтыков В.А.; Сенюков С.Л.; et al. (2016)
Жупановское землетрясение 30.01.2016 г. c Ks = 15.7, Mw = 7.2, I= 6 (Камчатка)